Effect of teachers' feedback on freshmen's motivation to learn writing skill - a survey research at Hanoi University of business and technology = Ảnh hưởng của việc phản hồi của giáo viên đến động lực học kĩ năng viết của sinh viên năm thứ nhất: Một nghiê - Nguyễn, Thị Hương Lan (University of Languages and International Studies, 2017)
60 p. + CD-ROM